Residual Risk, Trading Costs, and Commodity Futures Risk Premia: - Hirshleifer, David (Review of Financial Studies, 1988)
Trading costs, in the form either of explicit charges or of the costs of becoming informed, limit the participation of some classes of traders in commodity future markets. When speculators face a fixed cost of participating in a futures market that is used by commodity producers to hedge their stochastic revenues, the futures risk premium deviates from the perfect market prediction. The deviation rises in absolute value with the square root of the trading cost and with the standard deviation of residual returns, and it is unrelated to the covariance of the futures price with producers' nonmarketable wealths. The residual-risk premium depends not on the total magnitude of the risk that producers hedge (i.e., aggregate revenue variance), but on the variability of their revenue relative to its mean (i.e., the coefficient of variation). Hence, even a commodity that constitutes a minor fraction of aggregate consumption may have a large premium for residual risk if the revenue derived from it has a large coefficient of variation.